Legal Review of The Legality of Artificial Intelligence Creations in The Frame of Intellectual Property Rights in Indonesia - Nanda Dwi Purnama; Farhan Ammar Luthfi; Hafifah Nur Hasanah; Tubagus Bayu Pamungkas; Nova Auliyanti Faiza; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2024)
In this modern era, many technologies have emerged and help human life, one of which is Artificial Intelligence (AI), but despite the many benefits it brings, it turns out that AI also brings anxiety, especially in the field of Intellectual Property Rights (IPR), which Many AI creations are considered to have the potential to commit violations, especially in the field of copyright, such as forgery of works of art or theft of works of art. Apart from that, AI creation itself invites other problems regarding whether it can be legally protected or not, because one of the problems that exists in the use of AI is that the data used in its development uses existing creations, unless the copyright protection period has expired, then the creation is still subject to copyright protection. So that the legality of the AI creation itself is still questionable. Therefore, by using the normative method by collecting data related to relevant rules and opinions of experts, from these data, researchers try to analyze using descriptive analytical methods that connect the object under study with existing regulatory provisions and with literature studies, it is hoped that this article can answer the problem of the legality of AI creations, especially in the frame of Intellectual Property Rights in Indonesia. According to the Indonesian Copyright Law (UUHC), works created by Artificial Intelligence cannot be said to be works of creation that can be protected. However, legal violations that occur due to the use of AI can be held accountable by the AI service provider. To avoid the many violations that will occur in the future due to the continued development of this technology, the Indonesian government must make clearer and firmer regulations in regulating technological developments that are occurring rapidly and widely in Indonesia.